Implementation of Sustainable Purchasing at Hotel X - WIJAYA, I Kadek Agus Artha; SUMARIATI, I Dewa Ayu Rai; RUKMIATI, Ni Made Sri (Journal of Tourism Economics and Policy, 2025)
This study aims to analyze the implementation of sustainable purchasing at Hotel X based on the indicators listed in the Marriott International Responsible Sourcing Guide. Along with increasing awareness of sustainability issues and pressure from various stakeholders, the hotel industry is required to adopt environmentally friendly and socially responsible practices, including in the procurement process of goods and services. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and internal hotel documentation. The results show that the purchasing department of Hotel X has implemented four of the six main product categories focused on in the Marriott guide, namely animal protein (crate-free pork), bottled water (using recycled glass bottles and gallons), coffee (from suppliers with sustainable agriculture standards), and seafood (from certified suppliers). The other three categories, namely cocoa, sugar, and cage-free chicken eggs, have not been fully implemented due to limited supplies from local suppliers who have not met Marriott International's sustainability standards. These findings indicate that the hotel has demonstrated a strong commitment to environmental sustainability by considering environmental, social, and ethical aspects in the purchasing process. This implementation also reflects the principles of stakeholder theory, where the hotel strives to meet the expectations of stakeholders such as customers, suppliers, communities, and parent companies, and contributes to the achievement of sustainable development goals promoted by Marriott International globally.